Fatigue Crack Propagation in Aluminium 6063 Tubes - Oshkour, Azim Ataollahi (2009)
Tubular structures have extensive usage from domestic to aviation. Therefore estimate of life and safety are essential for design and use. Fatigue is one the most frequent cause for failure in components. Beside fatigue, external surfaces of structures are always in contact with environment and due to imperfection during product fabrication, surface crack may exist. Therefore surface crack is the most common form of crack in engineering structures. To overcome the fatigue problem the design approaches should be considered. The fatigue design approaches are divided in two categories which are safe life approach and damage tolerant design. Due to the importance of tubular structure and possible effect of fatigue in structural damage, the present work has focused on fatigue and fatigue crack propagation behavior in cylindrical structures. The fatigue design approaches utilized stress based safe life and damage tolerant design approach. The finite element software, ABAQUS used to analyze fatigue and determine fracture parameters. At the beginning fatigue test in finite life was carried out based on Japanese standard. The fatigue tests were done at room temperature and about 350°C under stress ratio equal to -1 and 0.1. Following experimental part, a 3-D fatigue analysis was carried out by ABAQUS. In fatigue analysis by ABAQUS, the linear material is considered and the results of finite element analysis are plotted in maximum stress versus number of cycles to failure graph. Fatigue analysis was carried out in same condition as experimental part at room temperature and 350°C under stress ratio equal to -1 and 0.1. Subsequent to fatigue analysis, the fatigue crack propagation tests were also carried out. The fatigue crack propagation test was carried out under increasing stress intensity factor or constant amplitude stress. In fatigue crack propagation test, a cracked tubular specimen was used. The crack is located in specimen by wire cut. The crack was an external and circumferential with straight front with depth of 0.37mm. The results of fatigue crack propagation were plotted in two types of graphs; first is crack length ,a, versus the number of cycles, N at each crack length and second is the crack growth rate which plotted as function of rate of crack length upon the number of cycles, da/dN versus the stress intensity factor as fracture parameter. Moreover ABAQUS was used to derive the fracture parameters. Two types 3-D tubes with crack were modeled. In first model assumed as sharp and thin crack, but in the second type the blunt crack considered. Material of tube in ABAQUS assumed to be a linear elastic and elastic prefect plastic. The results of crack modeling include fracture parameters as stress intensity factor, and Jintegral which were plotted as a function of crack front. The experimental results of fatigue showed a good agreement with finite element fatigue results. Based on fatigue results the fully reversed fatigue is more severe than fatigue with stress ratio equal to 0.1. Temperature does affect fatigue life which is shown by a decrease in yield strength and ultimate strength of material which resulted in reduction in the fatigue life of specimens with increasing temperature. The fatigue crack propagation results indicated crack growth rate in loading with stress ratio equal to 0.1 is more than stress ratio equal to -1. Crack first grew through the thickness followed by the surface of specimen. This was verified by the results from finite element that show maximum fracture parameters in the deepest point of the crack.